COREALATION ANALYSIS OF THE ANTROPOLOGCAL SPACE MOTOR AND COGNITIVE DIMENSIONS OF HIGH SCHOOL STUDENT - Milica Bešović; Elvira Beganović; Helena Bešović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
In order to affirm the correlation in anthropological space of psychomotor and cognitive abilities, and their connectivity to success in studying, research was conducted on a random sample of 200 female high school students. The sample had 7 sets of primary psychomotor indicators and also the sample was generally successful in studying. According to the criteria of the formal curriculum in education for kinesiology, the sample was being sub-sampled in increments of two to four hours per week. The correlation analysis was applied in order to correlate the psychomotor variable to the critical variable of success in studying. The assumption at the beginning of the experiment was proven true because there is significant connectedness between the system of psychomotor variable and the variable of general success in studying by female high school students. The research reaffirmed what previous scientific studies have found about the real connectedness of psychomotor and cognitive dimensions in anthropological space.